GESI bundle: Climate-Smart Agriculture for Sustainable Economic Participation & Inclusion & Livelihood (CSA-SEPAL Project) - Better World Innovation (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The main goal of the proposed project is to increase food and economic household security among Female Living with HIV (PLHIV), Women-led households, Gender-based Violence Survivors, and Young Women. The project proposal will empower 100 beneficiaries (10 cooperative groups of 10 members per group) in central province to engage in profitable and sustainable soya beans and groundnuts farming using good agronomic farming practices, enhanced utilization of climate information services and adoption of climate resilient seed varieties. This project is aimed at empowering 100 smallholder farmers to engage in profitable soya beans and groundnut farming through out-grower partnership. The 10 cooperative groups will cultivate 20 hectares of land to produce 90 tons of soya beans and 50 tons of groundnuts in the first season of the project.